Uncovering the Indigenous Khas Legacy of Resilience and Transformation in Western Nepal - Kafle, Dol Raj (KMC Journal, 2024)
This study explores the history and cultural resilience of the Khas Arya community in western Nepal. The purpose of the study is to investigate the changing patterns of the ancient indigenous Khas ritual culture, distinct from the Hindu Aryans of the south, due to their legacy of resilience and transformation. The research question centres on how the Khas Aryas have preserved their unique identity and rituals over time despite external influences. This study employed the qualitative research method and the historical research design using published documents as the data tools. The study reveals that the Khas community has been residing in western Nepal for thousands of years. They have maintained their distinct language, culture, and traditions, even as they embraced Hinduism and Buddhism. The Khas Aryas have preserved their original rituals, including nature worship and communal dining. The study highlights that they have retained their unique identity, distinct from the Hindu Aryans of the south, due to their historical resilience and cultural adaptation. The Khas Arya community's enduring legacy as an indigenous people of western Nepal reflects their ability to maintain their cultural identity in the face of external influences and changing times.